2016
DOI: 10.6000/2292-2598.2016.04.03.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Upper Extremity Motor Skills in Girls with Rett Syndrome Using Virtual Reality

Abstract: Introduction: Rett Syndrome is a genetic disorder that limits a girl's ability to use her upper extremities for daily activities, such as dressing and playing. One possible intervention to improve upper extremity function in this population is virtual reality, which can be used to increase activity demands during therapy sessions.Objectives: To determine the feasibility of using internet-based virtual reality intervention for Rett Syndrome (RTT-IVR), to decrease hand wringing/mouthing and increase hand and arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In their 2016 case series, Mraz and colleagues analyzed the feasibility of using an internet-based virtual reality intervention (FAAST software and Microsoft Kinetect sensor) for six girls with RTT [ 54 ]. The results showed decrease of hand stereotypes and increase of hand and arm movements away from the midline during intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their 2016 case series, Mraz and colleagues analyzed the feasibility of using an internet-based virtual reality intervention (FAAST software and Microsoft Kinetect sensor) for six girls with RTT [ 54 ]. The results showed decrease of hand stereotypes and increase of hand and arm movements away from the midline during intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The 2017 study by McAmis et al showed that the virtual reality system named VR_Color, specifically tailored for people with RTT, was able to decrease the characteristic repetitive hand movements and to increase the use of hands in skilled functions [ 55 ]. Moreover, this intervention proved to be successful in severe RTT cases, differently from the FAAST system, which has not been tested in the treatment of such patients [ 54 ].…”
Section: Resultsmentioning
confidence: 99%